MESSENGER observations of cusp plasma filaments at Mercury. Issue 9 (1st September 2016) - Poh, Gangkai; Slavin, James A.; Jia, Xianzhe; DiBraccio, Gina A.; Raines, Jim M.; Imber, Suzanne M.; Gershman, Daniel J.; Sun, Wei‐Jie; Anderson, Brian J.; Korth, Haje; Zurbuchen, Thomas H.; McNutt, Ralph L.; et al.
Abstract: The MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft while in orbit about Mercury observed highly localized, 3‐s‐long reductions in the dayside magnetospheric magnetic field, with amplitudes up to 90% of the ambient intensity. These magnetic field depressions are termed cusp filaments because they were observed from just poleward of the magnetospheric cusp to midlatitudes, i.e., 55° to 85°N. We analyzed 345 high‐ and low‐altitude cusp filaments identified from MESSENGER magnetic field data to determine their physical properties. Minimum variance analysis indicates that most filaments resemble cylindrical flux tubes within which the magnetic field intensity decreases toward its central axis. If the filaments move over the spacecraft at an estimated magnetospheric convection speed of 35 km/s, then they have a typical diameter of 105 km or 7 gyroradii for 1 keV H + ions in a 300 nT magnetic field. During these events, MESSENGER's Fast Imaging Plasma Spectrometer observed H + ions with magnetosheath‐like energies. MESSENGER observations during the spacecraft's final low‐altitude campaign revealed that these cusp filaments likely extend down to Mercury's surface. We calculated an occurrence‐rate‐normalized integrated particle precipitation rate onto the surface from all filaments of (2.70 ± 0.09) × 10 25 s −1 . This precipitation rate is comparable to published estimates of the total precipitation rate in the larger‐scale cusp. Overall, the MESSENGER observations analyzed here suggest that cusp filaments are the magnetospheric extensions of the flux transfer events that form at the magnetopause as a result of localized magnetic reconnection. Key Points: Cusp filaments form as plasma is injected down flux tubes at the magnetopause by localized reconnection Results indicate that cusp filaments map to flux transfer events at the magnetopause This result has important implications for surface sputtering and space weathering in the cusp region at Mercury